Communication—Effect of Micro-XCT X-ray Exposure on the Performance of Polymer Electrolyte Fuel Cells. Issue 10 (1st January 2016) - White, R. T.; Najm, M.; Dutta, M.; Orfino, F. P.; Kjeang, E.
Abstract : Exposure of polymer electrolyte fuel cells (PEFCs) to synchrotron radiation (SR) during in situ studies causes irreversible material damage and associated performance losses within minutes. Similar issues may be expected when PEFCs are exposed to X-rays in a micro-X-ray computed tomography (μ-XCT) system. The present work diagnoses the in situ performance and electrochemical active surface area during continuous exposure of a fuel cell in a μ-XCT. After 20 hours of X-ray exposure no degradation was measured. This significant difference can be attributed to the orders of magnitude lower X-ray photon flux during μ-XCT compared to SR.